2020
DOI: 10.1155/2020/7402163
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Birth Preparedness in Rapti Municipality of Chitwan, Nepal

Abstract: Introduction. Birth preparedness is crucial for health quality of mother and newborn and acts as a strong contributor in mitigating maternal and newborn mortalities. Different factors are predicted to have an influence upon birth preparedness practice. This paper aims at exploring relationship between various factors and birth preparedness practice. Methods. A cross-sectional study design was used to find out the relationship between various factors and birth preparedness practice. One hundred sixty-five women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
3
2
2
Order By: Relevance
“…Having knowledge of BP/CR increases the practice of BP/CR among pregnant women in this study. This is comparable with the studies from Benchi-Maji [ 43 ], Farta district [ 18 ], and Nepal [ 49 ]. The inference of this finding could be once women become knowledgeable about BP/CR, they are expected to practice the components of BP/CR and ready to act upon it when it occurs [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Having knowledge of BP/CR increases the practice of BP/CR among pregnant women in this study. This is comparable with the studies from Benchi-Maji [ 43 ], Farta district [ 18 ], and Nepal [ 49 ]. The inference of this finding could be once women become knowledgeable about BP/CR, they are expected to practice the components of BP/CR and ready to act upon it when it occurs [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the level of BP/CR in this study was lower than the study done in Uganda (53.9%) [ 25 ], Nigeria (81.5%) [ 47 ], Tanzania (95%) [ 48 ], Nepal (75.2%) [ 49 ], and Ethiopia (54.7%) [ 50 ]. The difference may attributable to the level of the study settings because those studies were only conducted at referral and teaching level hospitals.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The current study showed similar tendency even in the city area and the needs of education for the family. A study in Nepal supported that joint decision-making with the husband showed better preparedness [ 28 ]. Another research of a qualitative synthesis in 19 countries including both high-income and low/middle-income countries revealed strong influence of familial and sociocultural norms on decision-making; saying that women usually wish to retain a sense of personal achievement and control by being involved in decision-making [ 29 ].…”
Section: Discussionmentioning
confidence: 99%